Electron Transfer between Ruthenium (II)-(trisbipyridine) Ru and Cobalt(III)-(polypyridyl) Co at , , and Acetone Solvents - Mejbel, Hadi (University of Thi-Qar Journal of Science, 2013)
A theoretical calculations of electron transfer at metals interfaces are performed to study the electron transfer for Ru - Co system at ,, ,and acetone solvents. This study is basedon the assumption that metals have a continuum of donor's and acceptor's states .The rate of electron transfer,the reorganization energy ,the enthalpy , the effective free energy, and coupling coefficient of matrix elements ,V, were calculated for the donor Ru and acceptor in variety of solvents. The results show that the electron transfer in Ru system at solvents is fast and efficient. Our calculations show good agreement with the experimentally observed results for metals complex.